"Add up all my Black": understanding race and genetic ancestry through critical interpersonal and family communication. Issue 3 (3rd July 2021) - Peters, Charnell
ABSTRACT: Critical interpersonal and family communication (CIFC) contributes a context and lens for analyzing the intersections of race, communication, and genetic ancestry tests (GATs). This essay presents a discourse analysis of GAT reveal videos by Black content creators. Interpersonal communication—between the people in the videos and between them and online audiences—is a vehicle through which people narrate into meaning complex ideas of genetics and race. Results of this analysis show that Black content creators situate genetic ancestry within ongoing communication about identity. The videos work to "prove" Blackness and mark the significance of naming the self, often by conflating ideas of Blackness and genetic ancestry. CIFC as an analytic uncovers the paradox in which GAT discourse is both liberating and oppressive within relational spheres.